2014
DOI: 10.5090/kjtcs.2014.47.5.465
|View full text |Cite
|
Sign up to set email alerts
|

Post-Coronary Artery Bypass Grafting Myocardial Ischemia Caused by an Overgrown Left Internal Thoracic Artery Side Branch

Abstract: We present a patient who developed recurrent angina after coronary artery bypass grafting (CABG). Myocardial single-photon emission computed tomography (SPECT) demonstrated deterioration in the myocardial perfusion, and coronary angiography revealed an overgrown side branch of the grafted left internal thoracic artery (ITA); otherwise, there were no significant changes compared with previous imaging studies obtained after the CABG. After percutaneous embolization of the grafted left ITA side branch, the angina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In an analysis of 262 patients who underwent angiography before coronary artery bypass grafting (CABG) surgery, anomalies of the internal thoracic artery in the large side branch with a diameter greater than 30% of the LITA were present in 8.8% of patients [6]. Falconieri et al [7] reported on a patient with pseudoaneurysm of a branch of the LITA after cardiac surgery, and Kim et al [8] presented a case of post-CABG myocardial ischemia that was caused by an overgrown LITA side branch. However, there was no report of bleeding of the LITA branch due to pericardiocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 262 patients who underwent angiography before coronary artery bypass grafting (CABG) surgery, anomalies of the internal thoracic artery in the large side branch with a diameter greater than 30% of the LITA were present in 8.8% of patients [6]. Falconieri et al [7] reported on a patient with pseudoaneurysm of a branch of the LITA after cardiac surgery, and Kim et al [8] presented a case of post-CABG myocardial ischemia that was caused by an overgrown LITA side branch. However, there was no report of bleeding of the LITA branch due to pericardiocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 31 publications, 15 publications 57,59–72 had utilized coil embolization as the modality of percutaneous closure either as a stand‐alone method or in combination with other additional techniques.…”
Section: Elective Indications For Coil Embolizationmentioning
confidence: 99%
“…Coil embolization has long‐since been a therapeutic modality for vessel occlusion and has been shown to have a high technical success rate in numerous conditions, including cerebral aneurysms, systemic‐pulmonary collaterals, and coronary fistulas 43–45 . A large number of case reports describe total resolution of angina following coil embolization to LIMA side branches, with a high technical success rate 3,17,18,20,23,24,26,29–33,39,42,46,47 . In a large case series, Sbarouni et al 2 performed coil embolization in seven patients who had presented with stable angina with large unligated side branches, which all spanned at least 5–7 intercostal spaces.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…[43][44][45] A large number of case reports describe total resolution of angina following coil embolization to LIMA side branches, with a high technical success rate. 3,17,18,20,23,24,26,[29][30][31][32][33]39,42,46,47 In a large case series, Sbarouni et al 2 performed coil embolization in seven patients who had presented with stable angina with large unligated side branches, which all spanned at least 5-7 intercostal spaces. In five patients, complete occlusion of the branch was technically successful and resulted in total resolution of anginal symptoms.…”
Section: Coil Embolizationmentioning
confidence: 99%